Far-ultraviolet observations of NGC 4151 during the ORFEUS-SPAS II mission - ESPEY, BRIAN RUSSELL (American Astronomical Society, 1998)
We observed the Seyfert 1 galaxy NGC 4151 on 11 occasions at 1-2 day intervals using the Berkeley spectrometer during the ORFEUS-SPAS II mission in 1996 November. The mean spectrum covers 912-1220 A at ~0.3 A resolution with a total exposure of 15,658 s. The mean flux at 1000 A was 4.7x10^{-13} ergs cm-2 s-1 A-1. We identify the neutral hydrogen absorption with a number of components that correspond to the velocity distribution of H I seen in our own Galaxy as well as features identified in the C IV lambda 1549 absorption profile by Weymann et al. The main component of neutral hydrogen in NGC 4151 has a total column density of log NH I = 18.7+/-1.5 cm-2 for a Doppler parameter b=250+/-50 km s-1, and it covers 84%+/-6% of the source. This is consistent with previous results obtained with the Hopkins Ultraviolet Telescope. Other intrinsic far-UV absorption features are not resolved, but the C III* lambda 1176 absorption line has a significantly higher blueshift relative to NGC 4151 than the C III lambda 977 resonance line. This implies that the highest velocity region of the outflowing gas has the highest density. Variations in the equivalent width of the C III* lambda 1176 absorption line anticorrelate with continuum variations on timescales of days. For an ionization timescale of less than 1 day, we set an upper limit of 25 pc on the distance of the absorbing gas from the central source. The O VI lambda 1034 and He II lambda 1085 emission lines also vary on timescales of 1-2 days, but their response to the continuum variations is complex. For some continuum variations they show no response, while for others the response is instantaneous to the limit of our sampling interval.
PUBLISHED
Keywords: Physics